Building Democracy from Below: Lessons from Western Uganda. Issue 10 (3rd October 2017) - King, Sophie; Hickey, Sam
Abstract: How to achieve democratisation in the neo-patrimonial and agrarian environments that predominate in sub-Saharan Africa continues to present a challenge for both development theory and practice. Drawing on intensive fieldwork in Western Uganda, this paper argues that Charles Tilly's 'democratisation as process' provides us with the framework required to explain the ways in which particular kinds of association can advance democratisation from below. Moving beyond the current focus on how elite-bargaining and certain associational forms may contribute to liberal forms of democracy, this approach helps identify the intermediate mechanisms involved in building democracy from below, including the significance of challenging categorical inequalities, notably through the role of producer groups, and of building trust networks, cross-class alliances and synergistic relations between civil and political society. The evidence and mode of analysis deployed here help suggest alternative routes for supporting local efforts to build democracy from below in sub-Saharan Africa.